Exhibiting Cinema in Contemporary Art - Balsom, Erika (Film Culture in Transition, 2013)
Whether it involves remaking an old Hollywood movie, projecting a quiet 16mm film, or constructing a bombastic multi-screen environment, cinema now takes place not just in the movie theatre and the home, but also in the art gallery and the museum. The author of this engaging study takes stock of this development, offering an in-depth inquiry into its genesis, its defining features, and the ramifications it has for art and cinema alike. Through the lens of contemporary art history, she examines cinema studies' great disciplinary obsession - namely, what cinema was, is, and will become in a digital future.